Sosialisasi Umkm Go-Digital Dan Pelatihan Produksi Olahan Rambutan Di Desa Sumberagung, Boyolali - Muhammad Luthfi Maulana; Wahyu Susilo; Muhamad Deni Setiawan; Agung Wijayanto; Dea Novianingrum; Ferina Ruby Alfiyanti; Muhammad Fafatulriza; Muhammad Takbir Al-Farisi; Nabila Salsabila; Nani Siyamsih (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2022)
Community Service Program aim to find and make efforts that can optimize the role of the community in village development based on community empowerment. Sumberagung Village has a lot of potentials that can be developed, but due to lack of community knowledge, the existing potential cannot be developed properly. Examples are the use of rambutan fruit and the development of a marketing system for MSMEs. Based on this, the UNS Thematic KKN Group 74 took the initiative to hold training on the processing of rambutan seed chips and assistance in digitizing MSMEs. The activity was carried out using a mentoring and socialization approach by presenting material by speakers, asking questions, and discussing how to digitize the marketing system for MSMEs, which was then followed by training on the processing of rambutan seed chips which was attended by 17 participants. The result of this activity is to increase the knowledge of the people of Sumberagung Village in the field of digital marketing of business results and increase their skills in utilizing the potential around them.